Eco-Innovation Measurement by the European Observatory on Eco-Innovation (EIO) - Pawel BARTOSZCZUK (Communications of International Proceedings, 2020)
To date no uniform proposal for measuring and analysing eco-innovation in the literature has been emerged. The main challenges in this regard are the need to establish indicators at micro level, taking into account the life cycle and the separation of eco-efficiency from the economic category of eco-innovation, the definition of levels of eco-innovation analysis and the careful development of data aggregation methods, in addition to understanding the effect of eco-innovation and the relationship of eco-innovation indicators to key indicators for measuring sustainable and sustainable socio-economic development. The effects of eco-innovation can be measured on a micro scale (for product or service, process, enterprise), meso (sector,) and macro. Despite the high investment of companies, eco-innovation activities are producing results in the longer term on a micro scale by reducing the negative impact of its activities on the environment, while at the same time leading to the impact of eco-innovation on the company's performance in the form of lower environmental pollution charges and lower energy costs.
Keywords: Eco-Innovation; Eco-Innovation Activities; Eco-Innovation Observatory.